Dampak Penggunaan Keramba Jaring Apung pada Pembudidaya Ikan Kerapu Berdasarkan Perspektif Sosial Ekonomi - Lenny Widjayanthi; Yeni Anggun Widayanti (Jurnal KIRANA, 2020)
Grouper fish is a type of reef fish that is exported as a commodity to various countries such as Hong Kong, Japan, Singapore and China. Grouper fish can be cultivated using floating net cages and have a high selling price (high profit) but also have a high risk (high risk), thus affecting the market and the number of grouper aquaculture. The purpose of this research is to determine the socioeconomic impact of the use of floating net on grouper farmers. The determination of the research area was carried out deliberately in Situbondo Regency. The study was conducted with a qualitative approach. Data collection is done by observation and depth interview. The informants of the research were determined intentionally, namely grouper fish farmers who do aquaculture with floating net cages. The data analysis method uses Milles and Huberman. The results showed that the use of floating nets for grouper culture had social and economic impacts. The social impact on grouper farmers is the formation of grouper farmers, thus creating a social network in the form of interaction between farmers; construction of supporting facilities for the development of aquaculture businesses but also raises social prejudices between farmers because of frequent theft of fish in floating nets. While the economic impact is based on increasing grouper production which has a direct impact on the income of grouper farmers. Keywords : Floating net, grouper fish farmers, socio-economic impacts